Que sait-on de l’expérience existentielle des parents des jeunes contrevenants ? - Ambert, Anne-Marie; Gagnon, Louise (Criminologie, 1995)
This research on 116 parents of young offenders from the Montreal Centre area indicates that delinquency and its consequences have a negative impact on most parents. Basic statistics are presented for stress, fatigue, health, and general happiness. In addition, qualitative data from the young offenders' official files corroborate these results and offer more details concerning the areas of parents' lives that are affected. This paper examines the cultural and social reasons behind researchers' lack of interest in this topic. The study's results and limitations suggest a vast array of research questions.